VTPortal: a Scientific Community Web Portal for Reusable VisTrails Workflows - Cruz, Sérgio Manuel Serra da; Ribeiro, Alexandre; Mattoso, Marta (Anais do Brazilian e-Science Workshop (BreSci); 2011: Anais do V e-Science Workshop, 2011)
Managing large scientific experiments is a complex research challenge due to the amount of scientific resources to be managed. Science portals are a way to simplify this task by aggregating data from different sources and by providing a set of predesigned analyses. However, such portals are often built manually, and are not flexible enough to support sharing, reusing and executing workflows enacted by SWfMS like VisTrails. In this paper we describe VTPortal, a science portal that combines a set of tools and an infrastructure for providing a collaborative environment for scientists.